Critical Study of Research Results about TVET and TEFA’s Role in Social, Economic, and Education Development in the Country - Euis Ismayati; Supari Muslim; Nita Kusumawati; Erina Rahmadyanti; Moch Alfin Hilmi; Tri Wrahatnolo (JETL (Journal of Education, Teaching and Learning), 2020)
This study aims to determine the role of Technical Vocational Education and Training (TVET) and Teaching Factory (TEFA) on social, economic, and educational development in a country. The study was conducted using a literature review of some references and relevant research results of European countries, the United States (US), Africa, and Asia, especially in Indonesia. The results of the study obtained were presented in the Focus Group Discussion (FGD) to obtain input and criticism to improve the results of the research. The study concluded that: (1) TVET has a key and key role in the social, economic, and educational fields of a country; (2) the impact of TVET in Nigeria and other developing countries, in general, has not been impressive; (3) the application of TEFA has a positive and significant effect on work readiness of vocational students; and (4) the application of TEFA can contribute to the social, economic and educational development of a country.